Laboratory assessing of the liquefaction potential and strength properties of Sand soil treated with mixture of nanoclay and glass fiber under dynamic and static loading - Mohsen Sandiani (Journal of Materials Research and Technology, 2020)
This study evaluated an improvement method based on static and dynamic tests for dune sand soil on the coast of Bandar Anzali city. This soil has very poor and insufficient mechanical performance for many construction projects as well as the potential for liquefaction. Short glass fibers have been used in this improvement method to reinforce the soil modified with nanoclay. The effects of simultaneously adding glass fibers and modified nanoclay at optimal weight percentages on the sand specimen were evaluated through static triaxial tests at consolidated drained conditions. The results showed that the simultaneous addition of glass fibers and nanoclay at lower confining pressures had more significant effects and was more useful for soil modification. The results indicated increases of more than 31% and about 23% in the peak deviatoric stress of the modified sand specimen at the confining stresses of 50 and 100 kPa, respectively, compared to the pure sand specimen. Furthermore, the modified sand specimen had a 20% reduction and a 50% increase in failure axial strain, compared to the pure sand specimen, under the static triaxial test at the confining pressures of 50 and 200 kPa, respectively; however, its failure axial strain did not change at the confining pressure of 100 kPa compared to the pure sand specimen. The results of static triaxial tests showed that the simultaneous addition of glass fibers and nanoclay at the optimal weight percentages increased the cohesion of the sand specimen and did not change its internal friction angle. To investigate the effect of this improvement method on dune sand under dynamic loading, the cyclic liquefaction potential of pure and modified sand specimens was evaluated through cyclic triaxial tests under consolidated undrained conditions. The results showed a significant effect of sandy soil improvement on reducing its liquefaction potential. The number of loading cycles causing liquefaction was increased, by more than 5.5 times at the cyclic stress ratio of 0.27, by about 3 times at the cyclic stress ratio of 0.3, and finally, by more than 2 times at the cyclic stress ratio of 0.34 for the modified sand specimen compared to the pure sand specimen. By defining the cyclic stress ratio corresponding to liquefaction in the twentieth loading cycle as the specimen cyclic strength, the cyclic strength of the modified sand specimen was increased by more than 13% compared to the pure sand specimen. Based on the results of a series of different experiments conducted in this study, it was concluded that the simultaneous addition of glass fibers and modified nanoclay at their optimal weight percentages (0.5% and 1% by total dry weight of specimen, respectively) significantly improved many different resistance characteristics of dune sand soil from the Bandar Anzali coast, and using this composition can be considered as an effective and efficient way to improve this very special type of soil.